The Optimization of an Anti-VEGF Therapeutic Regimen for Neovascular Glaucoma - Bai, Ling; Wang, Yanfen; Liu, Xindi; Zheng, Yuping; Wang, Wenjing; He, Na; Tariq, Farheen; Wang, Feng; Zhang, Shu (Frontiers in Medicine, 2022)
This study investigates the safety and efficacy of conbercept injection through different routes for neovascular glaucoma (NVG) treatment, in which seventy-four patients (81 eyes) with NVG caused by ischemia retinopathy had participated. Patients were divided into three stages according to the progression of NVG and were randomly assigned to receive intracameral or intravitreal conbercept injection. After conbercept injection, patients experienced improved best-corrected visual acuity (BCVA), good intraocular pressure (IOP) control, and neovascularization of Iris (NVI) regression. In stage III, patients required trabeculectomy with mitomycin C plus pan-retinal photocoagulation (PRP) to achieve complete NVI regression. Compared to the intravitreal group, the intracameral group had significantly lower IOP in 2 days in stage III and 1 day in stages I and II after injection, complete NVI regression before PRP in stages I and II, and better NVI regression in stage III. The rates of hyphema after trabeculectomy and malfunction filtering bleb suffering needle bleb revision were lower in the intracameral group, but only the hyphema rate was significantly different. Injections through different routes are all safe. We recommend intravitreal injections for patients in stages I and II, but for stage III, intracameral injection is better, and trabeculectomy with mitomycin C should be conducted within 2 days after injection to maximally reduce the risk of perioperative hyphema. Trial Registration:ClinicalTrials.gov, identifier NCT03154892.